PERAN KKN TEMATIK POSDAYA BERBASIS MASJID AL HIDAYAH DALAM PENINGKATAN KEGIATAN MASYARAKAT DUSUN KRAJAN DESA SENEPOREJO - Atiqatul Musyarofah (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2018)
Real Work Lecture (KKN) is an intra-curricular activity by giving students a learning experience and working in community development activities as a vehicle for the application and development of science and technology which is carried out outside the campus in certain working time and technology mechanisms. Based on the above background, Thematic Posdaya based KKN based on Al Hidayah Mosque in Krajan Hamlet, Seneporeo Village, Silirangung Subdistrict, developed several community service programs aimed at improving the quality of public education. The type of data collected is primary data. Primary data is a variety of data and information obtained directly from informants and recommendations in the field that are administrators of takmir and from village officials. Posdaya in this mosque had never existed before, with the presence of KKN students from IAI Ibrahimy, the tile began to form the formation of POSDAYA masjid which Alhamdulillah was formed on July 26 2017 consisting of 12 members with 12 fields each, while the SK of Posdaya was attached to this report group report.